1980
DOI: 10.1002/j.1879-3479.1980.tb00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravaginal Administration of Conjugated Estrogens in Premenopausal and Postmenopausal Women

Abstract: Daily doses of 0.625 mg of conjugated estrogens were administered intravaginally for 14 days to 12 postmenopausal women (six with highly atrophic and six with slightly atrophic vaginal mucosa), resulting in vaginal mucosae similar to those found in premenopausal women in all 12 subjects. In a second experiment, serum estrogens, follicle-stimulating hormone (FSH) and luteinizing hormone (LH) were determined before and hourly for six hours after a single intravaginal dose of 0.625 mg of conjugated estrogens was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Up to now, no consensus has been achieved with regard to appropriate therapy: HRT should be given to women with menopausal complaints to meet their needs, taking into account their individual risk profile and the overall therapeutic objectives. Intravaginal oestrogen formulations have been introduced to avoid systemic exposure to oestrogens and are now preferred in women with no other menopausal symptoms requiring systemic treatment . However, the safety of local oestrogen treatment has been discussed, as data about the potential increase in serum levels of oestradiol with the use of vaginal tablets and creams are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, no consensus has been achieved with regard to appropriate therapy: HRT should be given to women with menopausal complaints to meet their needs, taking into account their individual risk profile and the overall therapeutic objectives. Intravaginal oestrogen formulations have been introduced to avoid systemic exposure to oestrogens and are now preferred in women with no other menopausal symptoms requiring systemic treatment . However, the safety of local oestrogen treatment has been discussed, as data about the potential increase in serum levels of oestradiol with the use of vaginal tablets and creams are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Para‐urethral punch biopsies, 6 mm in diameter and 10 mm in depth, were obtained from the SUI women during the TVT procedure, as described earlier (13). Corresponding biopsies were collected from the control patients during gynecological examination (1), or the respective operation (hysterectomy (5), laparoscopic operation of benign ovarian cysts (3), dilatation and curettage (2)).…”
Section: Methodsmentioning
confidence: 99%
“…The patients and controls were selected as above. The controls underwent hysterectomy (5), laparoscopic operation of ovarian cysts (3), and dilatation and curettage (2). See Table II regarding age, parity and hormonal use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that serum levels of other sex hormones and their binding proteins were not influenced can lead to the conclusion that there are no systemic actions at all, since especially the hepatic production of binding proteins is very sensitive to any estrogen effect. The decrease in E3-level after repeated vaginal application presumably is caused because of increased local metabolism within epithelial maturation, improved during the initial therapy: E3 absorption via a well-proliferated vaginal epithelium is markedly lower than that via an atrophic one [54,[84][85][86]. Derived from those pharmacokinetic studies it was suggested, that the use of 0.03-E3/L is safe without risk of endometrial or other systemic effects and may be considered for patients with a history of breast cancer and treated with aromatase inhibitors [84,87].…”
Section: Pharmacokinetics and Safetymentioning
confidence: 99%